Determination of depression and anxiety levels among parents of ADHD children - Oguzoncul, Ayse Ferdane; Kurt, Osman; Deveci, S. Erhan; Pirincci, Edibe; Yazici, Ipek Percinel (Bayrakol Medical Publisher, 2021)
Aim: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common psychiatric disorders of childhood. The aim of this study is to compare the depression and anxiety levels of parents of children with ADHD with a healthy control group. Material and Method: In this case-control study, cases were selected from the parents of patients aged 7-17 years who applied to Firat University Medical Faculty Child and Adolescent Psychiatry Outpatient Clinic, and the control group was selected from allied health personnel who had healthy children. A questionnaire consisting of questions investigating socio-demographic characteristics, the Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI) was applied to the participants. Results: The mean BDI score of the mothers in the case group was found to be 15.61 +/- 10.301, and the mothers of the control group was found to be 8.56 +/- 6.973, and a statistically significant difference was determined between them (p=0.001). The mean BAI score of the mothers in the case group was 14.20 +/- 10.442, the mean scoreof the mothers of the control group was found to be 8.90 +/- 8.516 and the difference was statistically significant (p=0.001). The mean BAI score of the fathers of boys with ADHD was significantly higher than the fathers of girls with ADHD. It was found that the mean BDI score of mothers increased significantly when the diagnosis period of children with ADHD was increased (p=0.004). The mean BDI and BAI scores of the mothers in the study group were significantly higher than the mothers in the control group. Discussion: In this study, no relationship was found between the ages of the mother and father and their level of depression and anxiety. In a study conducted by Ergin et al. with parents of disabled children, it was found that maternal age did not affect the level of depression [22]. In the study by Ozdel et al., they did not find a relationship between age and depression level in university students.
Keywords: Lack of attention; Hyperactivity disorder; Depression; Anxiety; Parent